New prospects of the integrative therapy for polycystic ovary syndrome in women with the disorders of carbohydrate and lipid metabolism: a comparative study. - Yu.E. Dobrokhotova; I.A. Lapina; T.G. Chirvon; V.V. Taranov (LCC «Medicine-Inform», 2020)
Yu.E. Dobrokhotova, I.A. Lapina, T.G. Chirvon, V.V. Taranov Pirogov Russian National Research Medical University, Moscow, Russian Federation Background: long-term combined estrogen-progestin oral contraceptive pills (COCPs) are the first-line treatment for polycystic ovary syndrome (PCOS). However, this therapeutic option does not affect metabolic disorders that are more severe in women with the second PCOS phenotype thus increasing the risk of cardiometabolic complications. Aim: to assess the effect of myo-inositol and D-chiro-inositol at a 5:1 ratio on metabolic parameters in women of reproductive age with the second PCOS pathogenetic type and the disorders of carbohydrate and lipid metabolism. Patients and Methods: 60 overweight and obese women with PCOS were enrolled in this randomized prospective study. Group 1 women (n=30) received COCP and a drug containing two isoforms of inositol at a 5:1 ratio (myo-inositol 1,000 mg plus D-chiro inositol 200 mg). Group 2 women (n = 30) received COCP only. Hemostasis, lipid panel, fasting glucose level, body mass index (BMI), and waist circumference were measur ed before and 90 days after treatment begins. Results: in group 1, the significant (p<0.05) improvement of lipid parameters was reported as demonstrated by the reduction of the levels of total cholesterol (TC) by 16.9%, triglycerides by 15.7%, low-density lipoprotein cholesterol (LDL-C) by 17.8%, fibrinogen by 15.8%, and fasting glucose by 16.9% as well as the increase of high-density lipoprotein cholesterol (HDL-C) by 28.5%. Meanwhile, no significant changes were seen in group 2. Additionally, the reduction of waist circumference by 4.5% and BMI by 9.1% was reported in group 1. Conclusions: a medication containing myo-inositol and D-chiro-inositol at a 5:1 ratio is promising for the prevention of cardiometabolic complications in women with PCOS. Further large studies of the investigated drug are needed to demonstrate its efficacy and to assess its properties. Keywords: polycystic ovary syndrome (PCOS), treatment, prevention, obesity, metabolic syndrome, lipid panel, inositol, oral contraceptive pills. For citation: Dobrokhotova Yu.E., Lapina I.A., Chirvon T.G., Taranov V.V. New prospects of the integrative therapy for polycystic ovary syndrome in women with the disorders of carbohydrate and lipid metabolism: a comparative study. Russian Journal of Woman and Child Health. 2020;3(3):169-173. DOI: 10.32364/2618-8430-2020-3-3-169-173.